Petrografia e geoquímica de gnaisses da região de Indiara, porção central do arco magmático de Goiás - Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; Montibeller, Cibele Carolina [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; De Morisson Valeriano, Claudio (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
In the region of Indiara, Goiás, there is an extensive belt of gneisses related to the Goiás Magmatic Arc, near the contact with the supracrustal rocks of the Anicuns-Itaberaí Metavolcanosedimentary Sequence. Although rocks from different locations associated with the Goiás Magmatic Arc have similar petrographic characteristics, geochemical and isotopic data show that the gneisses of Indiara region are not chemically similar to the rocks of type regions from the Arc (regions of Arenópolis, -Firminópolis, - Iporá and Mara Rosa). They have calcium-alkaline and peraluminous character, with predominantly granitic composition, in contrast to the prevalently calcic and metaluminous character of the type region, which also presents dominantly tonalitic to granodioritic compositions. The high SiO2 content, strongly peraluminous character and the high levels of normative corundum suggest that the gneisses of Indiara region are derived from Type-S syn-collisional granites and/or are related to mixing of igneous and sedimentary protoliths. TDM model ages (1.88 and 1.90 Ga) suggest that the gneisses of this region evolved from sialic crust older than the rocks that form the Goiás Magmatic Arc.
Petrography and geochemistry of gneisses from Indiara region, central portion of the Goiás magmatic arc
Keywords: Brasília belt; Gneisses; Tocantins Province